2013
DOI: 10.1186/1746-6148-9-67
|View full text |Cite
|
Sign up to set email alerts
|

Effect of somatic cell count and mastitis pathogens on milk composition in Gyr cows

Abstract: BackgroundGyr cows are well adapted to tropical conditions, resistant to some tropical diseases and have satisfactory milk production. However, Gyr dairy herds have a high prevalence of subclinical mastitis, which negatively affects their milk yield and composition. The objectives of this study were (i) to evaluate the effects of seasonality, mammary quarter location (rear x front), mastitis-causing pathogen species, and somatic cell count (SCC) on milk composition in Gyr cows with mammary quarters as the expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
4
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(89 citation statements)
references
References 18 publications
5
68
4
6
Order By: Relevance
“…Lower milk lactose observed during mastitis is in agreement with previous studies in dairy buffaloes (Bansal et al, 2007;Sharif Tripaldi et al, 2010;Hussain et al, 2012). Lower lactose content may be due to impairment of synthetic activity of mammary tissues or decomposition by leucocytes or mastitis causing pathogens or leakage from milk into blood (Hussain et al, 2012;Reis et al, 2013). Hence, lactose could be used as an indicator due to consistent change during intramammary infections (Tripaldi et al, 2010;Reis et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Lower milk lactose observed during mastitis is in agreement with previous studies in dairy buffaloes (Bansal et al, 2007;Sharif Tripaldi et al, 2010;Hussain et al, 2012). Lower lactose content may be due to impairment of synthetic activity of mammary tissues or decomposition by leucocytes or mastitis causing pathogens or leakage from milk into blood (Hussain et al, 2012;Reis et al, 2013). Hence, lactose could be used as an indicator due to consistent change during intramammary infections (Tripaldi et al, 2010;Reis et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Further, fat is considered as the most variable milk component, followed by protein and lactose is the least variable (Ravikala et al, 2014). On the other hand, during mastitis, alteration of milk lactose occurs markedly compared to other traits (Bansal et al, 2007;Sharif et al, 2007;Tripaldi et al, 2010;Hussain et al, 2012;Reis et al, 2013). Hortet and Seegers (1998) reviewed the alteration of milk fat and protein during mastitis and observed that the alterations were contradictory to several authors.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…La interpretación de esta variable debe tomar en cuenta otros factores que pueden influir, como el efecto de la genética (Demeter et al 2010), la etapa de lactancia (Stoop et al 2009), la duración del período seco (van KVan Knegsel et al 2014), la salud de la ubre (Malek dos Reis et al 2013), y el número de partos (Nayak et al 2012), por lo cual no debe considerarse el efecto aislado de cada uno en forma individual. Esto deja ver que la composición de la leche no es un indicador específico del estado nutricional, el cual debe ser analizado junto con otras variables que influyen significativamente en ella.…”
Section: Aspectos Teóricosunclassified